2022
DOI: 10.1002/ehf2.13919
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNAs are key predictors of long‐term heart failure and cardiovascular death after myocardial infarction

Abstract: Background Patients with acute myocardial infarction (MI) are at high risk of upcoming events, in particular heart failure (HF), but reliable stratification methods are lacking. Our goal was to evaluate the potential role of circulating miRNAs as prognostic biomarkers in patients presenting with MI. Methods and results We conducted a prospective study among 311 consecutive patients hospitalized with MI (65% ST‐segment elevation MI & median age of 55 years) with long‐term follow‐up. An initial screening was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
12
0
3
Order By: Relevance
“…Our findings pair well with previous evidence reported in other CV disorders. For instance, low to very low circulating miRNA 30a-5p levels predict sudden cardiac or arrhythmic death in patients with coronary heart disease [ 14 ]; an aberrant miRNA 23a-3p expression reflects the severity of ST-elevated myocardial infarction [ 17 ], predicts heart failure onset [ 39 ], and may help risk stratification for CV mortality and worsening New York Heart Association status in the long-term [ 40 ]. Finally, early deranged miRNA 451a levels anticipate acute coronary plaque rupture after percutaneous coronary intervention [ 26 ] and has prognostic value on the risk of transient or acute stroke in critically ill patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings pair well with previous evidence reported in other CV disorders. For instance, low to very low circulating miRNA 30a-5p levels predict sudden cardiac or arrhythmic death in patients with coronary heart disease [ 14 ]; an aberrant miRNA 23a-3p expression reflects the severity of ST-elevated myocardial infarction [ 17 ], predicts heart failure onset [ 39 ], and may help risk stratification for CV mortality and worsening New York Heart Association status in the long-term [ 40 ]. Finally, early deranged miRNA 451a levels anticipate acute coronary plaque rupture after percutaneous coronary intervention [ 26 ] and has prognostic value on the risk of transient or acute stroke in critically ill patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, low levels of miRNA-16, miRNA-27a and miRNA-150 appear to predict ventricular remodeling, whereas elevated levels of miRNA-208b, miRNA-34a, miRNA-21 and miRNA-155 correlate negatively with the same myocardial infarction consequences [ 237 , 238 , 239 , 240 ]. A recent study conducted by Rincón et al showed that the main outcome studied could be accurately predicted by miR-21-5p, miR-23a-3p, miR27b-3p, miR-122-5p, miR210-3p and miR-221-3p after a mean follow-up of 2.1 years in 311 consecutive patients hospitalized with MI [ 241 ]. Circulating microRNAs have thus displayed promising results as post-infarction prognostic biomarkers, and further research is needed to develop a risk assessment algorithm based on their levels in blood.…”
Section: Resultsmentioning
confidence: 99%
“…26 More recently, Rincón et al demonstrated the strong prognostic value of several miRNAs (miR-210-3p, miR-221-3p, and miR-23a-3p) in predicting long-term hospitalizations for HF and cardiovascular mortality among patients with MI. 27 Circulating miRNAs have also been proposed as useful biomarkers for the diagnosis of atrial fibrillation (AF) that is the most common form of arrhythmia among patients with cardiovascular diseases. The first data regarding the association between miRNAs and AF in the general population come from the Framingham Heart Study.…”
Section: Cardiac Mirna and Their Involvement In Heart Diseasementioning
confidence: 99%
“…More recently, Rincón et al . demonstrated the strong prognostic value of several miRNAs (miR‐210‐3p, miR‐221‐3p, and miR‐23a‐3p) in predicting long‐term hospitalizations for HF and cardiovascular mortality among patients with MI 27 …”
Section: Introductionmentioning
confidence: 99%